The relation of body image perception with body mass index, gender and disease activity in ankylosing spondylitis and rheumatoid arthritis (Annals of Medical Research, 2021)
None
Keywords: Rheumatoid Arthritis; Ankylosing Spondylitis; Body Image Perception.br /